The Model of Timeliness of Financial Reporting: the effect of Earnings Management and Firm Values - Winna Roswinna; Maria Lusiana Yulianti; Anne Lasminingrat (Greenation International Journal of Economics and Accounting, 2023)
The objective of this research is to examine the impact of Earnings Management on both Firm Value and the Timeliness of Financial Reporting within the manufacturing sector of companies listed on the Indonesia Stock Exchange between 2014 and 2017. This study incorporates three independent variables, namely Earnings Management (X1), Leverage (X2), and Profitability (X3), as well as two dependent variables, which are Firm Value (Y1) and Timeliness of Financial Reporting (Y2). In order to test the research hypothesis, Canonical Correlation Analysis is employed. The sampling technique utilized is purposive sampling, resulting in a total sample size of 104, representing 26 manufacturing companies over a consecutive 4-year period. The findings of the analysis and testing indicate that, when controlling for leverage and profitability, earnings management has a significant impact on firm value, but not on the timeliness of financial reporting.